Looking backward in order to move forward: The Chicago courtyard apartment building - Gnat, Richard (Kansas State University, 2009)
This paper examines the planning flexibility and the passive ventilation and lighting potential of the Chicago courtyard apartment building type through a systematic type / variant analysis of built examples. In an era of increasingly expensive energy the advantages of the passive ventilation and lighting strategies inherent in these pre-air conditioned designs becomes apparent. The basic courtyard building type is defined and documented through drawings and with historic and contemporary images. The base courtyard building type is compared and contrasted with the variants. In addition, the urban condition of the basic building type and variants is documented in figure ground and Nolli type maps. These maps are used to illustrate the variety of urban conditions in which Chicago courtyard apartment buildings are successfully integrated. Data have been collected from archives, the City of Chicago Planning Department, periodicals and from field investigations. This research will illustrate how the historic courtyard type responds successfully to a variety of urban conditions while providing ample natural ventilation and lighting making it a model type for contemporary multi-unit housing design.
Keywords: Lighting; Multi-unit housing; Housing; Chicago (Ill.); Ventilation; Apartment buildings